Effects of Cudrania tricuspidata on anti‐senescence in high glucose‐treated endothelial cells via the Akt/p53/p21 pathway - Kim, Gi Dae (Food Sci Nutr, 2020)
The roles of Cudrania tricuspidata (CT) in the prevention of senescence and the underlying mechanisms have not been elucidated. In a high glucose (HG)‐induced senescent endothelial cell (EC) culture, CT (20 µg/ml) reduced the number of senescence‐associated β‐galactosidase‐positive cells by 8.3% compared with the control group and increased the expression of p‐Sirt1 by more than twofold compared with the control group. Moreover, 20 μg/ml CT treatment doubled the activity of p‐Akt, which was inhibited by HG, compared with the control group. In addition, CT treatment decreased the expression of p53, p21, and Rb, which was increased by HG. Overall, CT delays HG‐induced senescence via the Akt/p53/p21 pathway, suggesting its potential as a functional agent for the protection of ECs.